PENGARUH MANAJEMEN LABA, ASIMETRI INFORMASI, DAN PENGUNGKAPAN SUKARELA TERHADAP BIAYA MODAL EKUITAS - Dian Desty Widyowati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2020)
The research method used multiple regression analysis. The data used are the annual financial statements of property companies listed on the Indonesia Stock Exchange 2014-2016. The sample is 87 companies with purposive sampling technique. The data is processed using SPSS (Statistical Product and Service Solution) Version 22. The results of this study indicate that earnings management has a positive effect on the cost of equity capital with a significant level of 0.000 and beta 0.712, information asymmetry has a significant effect on the cost of equity capital with a significant level of 0.087 and beta 0.139. , then voluntary disclosure has no significant effect on the cost of equity capital with a significant level of 0.955 and beta 0.004. In general, it can be concluded that earnings management has a positive effect on the cost of equity capital, while information asymmetry and voluntary disclosure have no significant effect on the cost of equity capital. Future studies consider adding other independent variables that can affect the cost of equity capital so that it can show a better correlation between the dependent and independent variables.